A Qualitative Evaluation of Mental Health Clinic Staff Perceptions of Barriers and Facilitators to Treating Tobacco Use. Issue 10 (7th September 2017) - Rogers, Erin S; Gillespie, Colleen; Smelson, David; Sherman, Scott E
Abstract: Introduction: Veterans with mental health disorders smoke at high rates, but encounter low rates of tobacco treatment. We sought to understand barriers and facilitators to treating tobacco use in VA mental health clinics. Methods: This qualitative study was part of a trial evaluating a telephone care coordination program for smokers using mental health services at six VA facilities. We conducted semi-structured interviews with 14 staff: 12 mental health clinic staff working at the parent study's intervention sites ( n = 6 psychiatrists, three psychologists, two social workers, one NP), as well as one psychiatrist and one psychologist on the VA's national tobacco advisory committee. Interviews were transcribed and inductively coded to identify themes. Results: Five "barriers" themes emerged: (1) competing priorities, (2) patient challenges/resistance, (3) complex staffing/challenging cross-discipline coordination, (4) mixed perceptions about whether tobacco is a mental health care responsibility, and (5) limited staff training/comfort in treating tobacco. Five "facilitators" themes emerged: (1) reminding mental health staff about tobacco, (2) staff belief in the importance of addressing tobacco, (3) designating a cessation medication prescriber, (4) linking tobacco to mental health outcomes and norms, and (5) limiting mental health staff burden. Conclusions: VA mental health staff struggle with knowing that tobacco use is important, but they face competing priorities, encounter patient resistance, are conflicted on their role in addressing tobacco, and lack tobacco training. They suggested strategies at multiple levels that would help overcome those barriers that can be used to design interventions that improve tobacco treatment delivery for mental health patients. Implications: This study builds upon the existing literature on the high rates of smoking, but low rates of treatment, in people with mental health diagnoses. This study is one of the few qualitative evaluations of mental health clinic staff perceptions of barriers and facilitators to treating tobacco. The study results provide a multi-level framework for developing strategies to improve the implementation of tobacco treatment programs in mental health clinics.